PENGARUH LITERASI KEUANGAN, GAYA HIDUP, GENDER DAN PERENCANAAN KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA UMS - Khotimah, Aisyiyah Nur Kusnul; Ariani, Kurnia Rina (ITB AAS Indonesia Surakarta, 2025)
In the era of globalization, financial management is an important aspect, especially for students who face various financial challenges such as education costs and living needs. Students need good financial understanding and knowledge to support effective financial management. Financial literacy, which includes an understanding of savings, loans, insurance, and investments, is one of the main factors that influence financial management behavior. This literacy helps individuals make optimal use of financial resources, make wise decisions and avoid financial risks. In addition, lifestyle also plays a role in financial management, as it reflects consumption patterns and habits that can change according to trends. With high financial literacy and proper lifestyle management, students can manage finances intelligently and minimize financial risks. This study aims to analyze the effect of Financial Literacy, Lifestyle, Gender and Financial Planning on the Financial Management Behavior of Students. This study uses multiple regression analysis with the help of the IBM SPSS program. The results of the study are Financial Literacy, Lifestyle, Financial Planning has a positive and significant effect on financial management behavior on students of Universitas Muhammadiyah Surakarta, while Gender has no positive and significant effect on financial management behavior on students of Universitas Muhammadiyah Surakarta.